Introduction—Topic models: What they are and why they matter - Mohr, John W.; Bogdanov, Petko (Poetics (Amsterdam), 2013)
We provide a brief, non-technical introduction to the text mining methodology known as “topic modeling.” We summarize the theory and background of the method and discuss what kinds of things are found by topic models. Using a text corpus comprised of the eight articles from the special issue of Poetics on the subject of topic models, we run a topic model on these articles, both as a way to introduce the methodology and also to help summarize some of the ways in which social and cultural scientists are using topic models. We review some of the critiques and debates over the use of the method and finally, we link these developments back to some of the original innovations in the field of content analysis that were pioneered by Harold D. Lasswell and colleagues during and just after World War II.